INSUFISIENSI ADRENAL PADA PASIEN DENGAN PENYAKIT KRITIS - Mariadi, I Ketu; Gotera, Wira (journal of internal medicine; Vol. 8, No. 1 Januari 2007, 2012)
Stress from many sources, including pain, fever, and hypotension, activates the hypothalamic-pituitary-adrenal (HPA) axis with the sustained secretion of corticotropin and cortisol. Increased glucocorticoid action is an essential component of the stress response, and even minor degrees of adrenal insufficiency can be fatal in the stressed host. HPA dysfunction is a common and underdiagnosed disorder in the critically ill. We review the risk factors, pathophysiology, diagnostic approach, and management of HPA dysfunction in the critically ill
Keywords: hypothalamic-pituitary-adrenal, insuficiency